Sex Differences in Stroke Subtypes, Severity, Risk Factors, and Outcomes among Elderly Patients with Acute Ischemic Stroke - Yu, Changshen; An, Zhongping; Zhao, Wenjuan; Wang, Wanjun; Gao, Chunlin; Liu, Shoufeng; Wang, Jinghua; Wu, Jialing (Frontiers in Aging Neuroscience, 2015)
Background: Although the age-specific incidence and mortality of stroke is higher among men, stroke has a greater clinical effect on women. However, the sex differences in stroke among elderly patients are unknown. Therefore, we aimed to assess the sex differences in stroke among elderly stroke patients. Methods: Between 2005 and 2013, we recruited 1,484 consecutive acute ischemic stroke patients (≥75 years old) from a specialized neurology hospital in Tianjin, China. Information regarding their stroke subtypes, severity, risk factors, and outcomes at 3 and 12 months after stroke were recorded. Results: Comparing with men, women had a significantly higher prevalence of severe stroke (17.20% vs. 12.54%), hypertension (76.42% vs. 66.39%), dyslipidemias (30.35% vs. 22.76%), and obesity (18.40% vs. 9.32%), P < 0.05. Comparing with women, men had a significantly higher prevalence of intracranial artery stenosis (23.11% vs. 17.45%), current smoking (29.60% vs. 13.05%), and alcohol consumption (12.15% vs. 0.47%), P < 0.05. Moreover, dependency was more common among women at 3 and 12 months after stroke, although the sex difference disappeared after adjusting for stroke subtypes, severity, and risk factors. Conclusions: Elderly women with acute ischemic stroke had more severe stroke status and worse outcomes at 3 and 12 months after stroke. Thus, elderly female post-acute ischemic stroke patients are a crucial population that should be assisted with controlling their risk factors for stroke and changing their lifestyle.